Nano Silicon Modulates Chemical Composition and Antioxidant Capacities of Ajowan (Trachyspermum ammi) Under Water Deficit Condition - Zahra Sobatinasab; Mehdi Rahimmalek; Nematollah Etemadi; Antoni Szumny (Foods)
Ajowan (Trachyspermum ammi) is an important spice in the food industry, as a well as a medicinal plant with remarkable antioxidant properties. In this study, its essential oil content, chemical composition, flavonoid content, phenolic content, and antioxidant capacity were evaluated under three irrigation regimes (50, 70, and 90% field capacity) and different amounts of nano silicon (0, 1.5, and 3 mM) in ten populations of ajowan. Based on the GC–MS analysis, thymol, carvacrol, p-cymene, and γ-terpinene were determined as the main components of the oil. The thymol content ranged from 34.16% in the Ardabil population (irrigation at 50% and nano silicon at 1.5 mM) to 65.71% in the Khorbir population (without nano silicon and irrigation at 50%). The highest phenolic content was in Khormo with irrigation at 90% and without nano silicon (172.3 mg TAE/g DW), while the lowest was found in Hamedan (irrigation at 50% and without nano silicon (7.2 mg TAE/g DW)). Irrigation at 50% and no nano silicon treatment led to an increase in total flavonoids in Ardabil (46.786 mg QUE/g DW). The antioxidant activity of ajowan was evaluated using the DPPH assay. Accordingly, the highest antioxidant capacity was observed in Khormo (irrigation at 90% without nano silicon; 4126 µg/mL). Moreover, the highest thymol content was observed in the Khorbir population with irrigation at 50% and without nano silicon treatment. Furthermore, correlation and principal component analysis (PCA) provide new insights into the production of ajowan from their substrates under nano silicon treatment and water deficit conditions. Finally, the results revealed information on how to improve the desired essential oil profile and antioxidant capacity of extracts for industrial producers.